View of Moralization: Study on Confucian Moral Thought - Ge, Chenhong (Springer eBook Collection, 2020)
Chapter I Consanguineous Foundation and Peculiarity of Moral Thought -- Chapter II Moral Thought in Nature -- Chapter III Moral Thought of Human Itself -- Chapter IV Moral Thought in Social Sector -- Chapter V Development of Moral Thought and its Fundamental Value Orientation -- Chapter VI Moral Thought and Chinese Traditional Culture -- Conclusion.